Real and nominal rigidities in price setting: A bayesian analysis using aggregate data - Fang Yao (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
This paper uses the Bayesian approach to solve and estimate a New Keynesian model augmented by a generalized Phillips curve, in which the shape of the price reset hazards can be identified using aggregate data. My empirical result shows that a constant hazard function is easily rejected by the data. The empirical hazard function for post-1983 periods in the U.S. is consistent with micro evidence obtained using data from similar periods. The hazard for pre-1983 periods, however, exhibits a remarkable increasing pattern, implying that pricing decisions are characterized by both time- and state-dependent aspects. Additionally, real rigidity plays an important role, but not as big a role as found in empirical studies using limited information methods.
Keywords: E12; E31; 330; Real rigidity; Nominal rigidity; Hazard function; Bayesian estimation; Preisrigidität; Statistische Bestandsanalyse; Bayes-Statistik; Ungleichgewichtstheorie; Phillips-Kurve; Schätzung; USA